Comparative analysis of lip with thumbprints: An identification tool in personal authentication - Naik, Rashmi (J Oral Maxillofac Pathol, 2017)
CONTEXT: Identification of person living or dead using diverse characteristics is the basis in forensic science. The uniqueness of lip and fingerprints and further, association between them can be useful in establishing facts in legal issues. AIMS: The present study was carried out to determine the distribution of different lip print patterns among subjects having different thumbprint patterns and to determine the correlation between lip print patterns and thumbprint patterns. MATERIALS AND METHODS: The study sample comprised 100 students randomly selected from Bapuji Dental College Hospital, Davangere, Karnataka, 50 males and 50 females aged between 18 and 20 years. Red colored lipstick was applied on the lips by a lipstick applicator brush. Lip and thumb impressions were made on No. 1 Whatman filter paper and visualized using magnifying lens. Three main types of fingerprints (loop, whorl and arch) were identified; Tsuchihashi Y classification of lip print patterns was followed in the study. Chi-square test was used to see the association between lip and thumbprints. RESULTS: The correlation between lip and left thumb print patterns for gender identification was statistically significant. In both males and females, Type II lip pattern associated with loop finger pattern were most significant and in males, Type III lip pattern with whorl type of finger pattern showed statistical significance. CONCLUSION: We conclude that the correlation found between lip print and thumbprint can be utilized in the field of forensic science for gender identification.